The Relationship Between Self-Regulation, Parent-Adolescent Attachment and Self-Concept With Online Game Addiction - Oktavia, Lyanna; Sugiyo, Sugiyo; Awalya, Awalya (Jurnal Bimbingan Konseling, 2021)
The ease of internet access enables a lot of students to play online games. However, if the online games are uncontrollably played, students will get addicted. This study aimed to determine the relationship between self-regulation, parent-adolescent attachment, and self-concept with online game addiction tendency by Public Senior High School students in Semarang City amounted to 391 people. Quota random sampling and self-regulation questionnaire adopted from Miller & Brown (1991), attachment scale adopted from Gullone and Robinson (2005), self-concept scale (Tennessee Self-Concept Scale) from Burn (1993), and online game addiction from Lemmens (2009) were used to sample the students. Findings showed that the online game addiction tendency by the students of Public Senior High School in Semarang City was low. Further, the researchers found that self-regulation, attachment, and self-concept had negative and significant relationships with online game addiction. To follow-up these findings, prevention needs to be addressed to online game addiction by strengthening self-regulation, positive self-concept and building parents and adolescents interactions.